A QUALITATIVE RESEARCH OF CLASH OF CLANS ONLINE GAME AND ITS RELATION WITH EMPLOYEE PERFORMANCE IN PT. HONDA REMAJA JAYA MOBILINDO - Mawey, Stevie N.; Tumiwa, Johan (FEB Universitas Sam Ratulangi Manado, 2016)
Clash of clans online game recently gain much attention from many people. Many research convinced that online game have negative effects on employee performance. Playing online game at work is not discouraged there is evidence that work hours increases productivity and that online game can be beneficial. This research is designed to clearer image and deeper understanding that online game could reduce stress while break hours. The method used in this research is the qualitative research methodology with case study research approach which will provide a descriptive insight about clash of clans online game and its relation with employee performance. The data for this research were gathered from observation, interviews, and documents, with 10 people participant in PT. Honda Remaja Jaya Mobilindo to get a comprehension about clash of clans online game. In the finding, there are several perspective about clash of clans online game but the main point is playing clash of clans online game in break hours could reduce stress. The employee should use break time to playing online game in order for reduce stress in work place. Keywords: clash of clans, game online, employee performance